Islamic Dakwah Movement (IDM) in Malaysia: the case of Pertubuhan IKRAM Malaysia - Malik, Maszlee; Mat, Hamidah (UIN Sunan Ampel Press, 2016)
Over the last few decades, the contribution of Islamic Dakwah movement (IDM) in development and reform agenda has gained recognition, both locally and internationally. IDMs appear to be important actors in many developing countries. IDMs are usually characterized as independent from the government, involved in non-profit making activities and fighting for specific causes. This study aims to explore the dynamic roles of IDM in leading the changes and reforms in the modern society and how Islamic organizations could fit into the framework by critically looking into the experiences of Pertubuhan IKRAM Malaysia (IKRAM), a Malaysian-based Islamic organization as a case study. While the results reveal some positive impacts on the society, they also exhibit a number of challenges and conflicts when the evolution reaches certain stages of time and space, illustrating the dynamic nature of IKRAM as both an Islamic organization and NGO with regards to strategies, resources and strategic actions.